Microwave-assisted drying of stingless bee (tetragonula biroi) pollens - Miranda, Franz Z.; Somera, Carolyn Grace G.; Cinense, Marvin M.; Lavarias, Jeffrey A. (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the study was to evaluate the effect of microwave drying to the quality of stingless bee pollens. A microwave oven was modified to have an air circulating facility for drying purposes. Fresh bee pollens were analyzed for baseline data. The bee pollens were microwave dried in different power outputs (119W, 336W, and 700W), and then these were characterized to determine the drying characteristics and changes in its quality. The microwave dryer has an overall dimension of 300 x 450 x 500mm (LxWxH). Results showed that 700W power output has the best performance compared to 336W and 119W in terms of drying time (5 mins), drying capacity (1.8kg/hr), and moisture reduction rate (108.421%/hr). Based on the analysis, fresh bee pollens has 12.07% moisture, pH of 4.04, water activity of 0.622, 16% w/w of protein, • mg/100g of vitamin E, and 118mg/100g of β-carotene. After drying, the 336W treatment has the highest protein content of 16.3% w/w compared to 700W with 16.1% w/w. In vitamin E, 119W has 0.95mg/100g which was lower than the value of fresh samples while in 700W and 336W, vitamin E increases with 2.8 and 1.7mg/100g, respectively. All treatments show an increase in β-carotene with 700W as the highest (0.226mg/100g) and 336W with the lowest (0.174mg/100g).